Comparison of Effectiveness and Growth Performance in Zakat Institutions: Insight from Indonesia - Zakiy, Faris Shalahuddin; Falikhatun, Falikhatun (Universitas Syiah Kuala, 2023)
Objective This research aims to compare the effectiveness and growth performance of zakat institutions before and during Covid-19 in Indonesia.Design/Methodology This study uses a quantitative approach. The 2018 and 2019 financial performance represents conditions before Covid-19, while the 2020 and 2021 financial performance represents conditions during Covid-19. This research examined 26 zakat institutions, with 104 observations. The performance examined in this research includes net allocation to collection ratio (NACR), zakat allocation ratio (ZAR), infaq shadaqa allocation ratio (ISAR), and growth of ZIS collection (GZIS). Data analysis in this study used paired sample t-test.Results The research results show no difference in the performance of NACR, ZAR and ISAR before and during Covid-19. Meanwhile, there are differences in GZIS performance before and during Covid-19. Collection growth tends to decrease during Covid-19 compared to before Covid-19.Research limitations/implications Zakat institutions must be able to create utilization programs that are right on target and make distribution of collections more effective, so that people have more trust and donate their funds to zakat institutions. Transparency in the performance of zakat institutions increases public trust, so zakat institutions become the institution of choice for the community to manage zakat funds.Novelty/Originality This research uses secondary data and statistical tests to measure the comparative performance of zakat institutions, which is still rarely done. This research provides an overview of empirical results comparing the performance of zakat institutions before and during Covid-19.